2008
DOI: 10.1039/b803827a
|View full text |Cite
|
Sign up to set email alerts
|

Water-oil core-shell droplets for electrowetting-based digital microfluidic devices

Abstract: Digital microfluidics based on electrowetting-on-dielectric (EWOD) has recently emerged as one of the most promising technologies to realize integrated and highly flexible lab-on-a-chip systems. In such EWOD-based digital microfluidic devices, the aqueous droplets have traditionally been manipulated either directly in air or in an immiscible fluid such as silicone oil. However, both transporting mediums have important limitations and neither offers the flexibility required to fulfil the needs of several applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 36 publications
1
72
0
Order By: Relevance
“…8, we thus made simulations of transport processes with these values of the contact angles. We found an average velocities of about 40 cm/s, which is at least 2-3 times larger than experimental velocities achieved in similar real EWOD devices (Brassard et al 2008). We believe this discrepancy between the LBM simulations and the velocities values obtained in real EWOD devices is due to CAH (that was not considered in the simulations).…”
Section: Transport Velocitymentioning
confidence: 57%
See 3 more Smart Citations
“…8, we thus made simulations of transport processes with these values of the contact angles. We found an average velocities of about 40 cm/s, which is at least 2-3 times larger than experimental velocities achieved in similar real EWOD devices (Brassard et al 2008). We believe this discrepancy between the LBM simulations and the velocities values obtained in real EWOD devices is due to CAH (that was not considered in the simulations).…”
Section: Transport Velocitymentioning
confidence: 57%
“…6. Thus, we conclude that despite the low density ratios usually obtained in multiphase lattice Boltzmann simulations, the To compare our simulation results with the values obtained in real EWOD devices, we should first note that real devices typically operate with rather small differences between ON and OFF contact angles (Brassard et al 2008) compared to the simulations we showed previously. For example, a pair of contact angles often employed in real EWOD devices is 110°for the OFF state (inactive regions on the plates) and 80°for the active electrodes (ON states).…”
Section: Transport Velocitymentioning
confidence: 83%
See 2 more Smart Citations
“…Immersing the water droplet in oil increases the contact angle [62] and reduces contact angle hysteresis, which makes it possible to insert droplets into channels with a smaller radius and makes vertical functionality easier to achieve (Figure 6b).…”
Section: Characterization Of Droplet Forces and Design Parametersmentioning
confidence: 99%